PENGEMBANGAN MODUL TRIGONOMETRI UNTUK MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Rahmatya Nurmeidina; Ahmad Lazwardi; Arif Ganda Nugroho (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Problem-solving is one of the most important abilities possessed by prospective mathematics teacher students. One way to develop student problem-solving abilities is to use learning models designed to develop problem-solving abilities. This study aims to develop a trigonometry module to develop valid, practical, and effective mathematics education student problem-solving abilities. This research is a research development (Research & Development). This study develops a trigonometric course module using the 4D development model (Define, Design, Develop, Disseminate). The instruments used consisted of validation sheets filled out by experts in the field of mathematics education, student practicality assessment sheets, and learning outcomes tests with problem-solving questions. The quality of the developed modules is viewed from the aspects of validity, aspects of practicality, and aspects of effectiveness. The result is that the module is included in the valid category, with a high practicality value. The aspect of effectiveness based on test learning outcomes with problem-solving problems has increased from the results of the pretest and posttest. The result of the development in this study is the product of a trigonometric course learning module that is valid, practical and effective, and suitable for use by mathematics education students. The contribution of this research is that this module can be used during Trigonometry lectures.